2016
DOI: 10.1007/s11262-016-1366-2
|View full text |Cite
|
Sign up to set email alerts
|

Influenza A Virus-induced expression of ISG20 inhibits viral replication by interacting with nucleoprotein

Abstract: Influenza A virus (IAV) is an important pathogen that has a wide range of hosts and represents a threat to the health of humans and several animal species. IAV infection can induce the transcription of many genes in the host. In the present study, we demonstrated for the first time that three different strains of H1N1 IAV induce the expression of an IFN-stimulated gene, ISG20. We determined the antiviral activity of ISG20 against IAV because ISG20 inhibited viral protein expression and reduced the progeny vira… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
43
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 44 publications
(46 citation statements)
references
References 43 publications
1
43
0
Order By: Relevance
“…RuvB-like protein 2 disrupts vRNP assembly by interfering with NP oligomerization (34). Interferon-stimulated gene 20 interacts with NP and inhibits viral protein expression (35). Similarly, our study showed that TRIM41 modulates IAV infection by interaction with NP, which allows NP ubiquitination and subsequent protein degradation.…”
Section: Discussionsupporting
confidence: 54%
“…RuvB-like protein 2 disrupts vRNP assembly by interfering with NP oligomerization (34). Interferon-stimulated gene 20 interacts with NP and inhibits viral protein expression (35). Similarly, our study showed that TRIM41 modulates IAV infection by interaction with NP, which allows NP ubiquitination and subsequent protein degradation.…”
Section: Discussionsupporting
confidence: 54%
“…However, RNA degradation might not be the only mechanism of ISG20's antiviral action. For instance, Zhou et al found that ISG20 did not promote the degradation of a replication-defective HCV RNA genome in Huh7.5 cells [17]; and Qu et al observed that ISG20 inhibits Influenza A Virus replication through interaction with viral nucleoproteins [37]. Furthermore, not all the RNA viruses are susceptible to ISG20, as severe acute respiratory syndrome coronavirus (SARS-CoV) has shown resistance to ISG20 in cell cultures [17], indicating that there is viral specific factor(s) to determine the antiviral specificity of ISG20.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, ISG20, a member of the 3=-to-5= exonuclease superfamily, displays effective antiviral activity against several RNA viruses, including IAV, vesicular stomatitis virus (VSV), hepatitis C virus (HCV), and encephalomyocarditis virus (EMCV), mostly relying on its RNase activity (12)(13)(14)(15)(16). In addition, ISG20 inhibits IAV replication by interacting with viral NP protein and inhibiting viral polymerase activity (17).…”
Section: Importancementioning
confidence: 99%